2012
DOI: 10.1073/pnas.1214141109
|View full text |Cite
|
Sign up to set email alerts
|

Genetic composition of yield heterosis in an elite rice hybrid

Abstract: Heterosis refers to the superior performance of hybrids relative to the parents. Utilization of heterosis has contributed tremendously to the increased productivity in many crops for decades. Although there have been a range of studies on various aspects of heterosis, the key to understanding the biological mechanisms of heterotic performance in crop hybrids is the genetic basis, much of which is still uncharacterized. In this study, we dissected the genetic composition of yield and yield component traits usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
213
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(227 citation statements)
references
References 47 publications
8
213
1
1
Order By: Relevance
“…The number of panicles ranges between 9.6 (HB4) and 27.3 (HB2) panicle per plant. The average number of seeds per panicle, the most importance contributor to heterosis for high yielding hybrids 20 , ranges from 158.8 (HB9) to 323.3 (HB7). Seyoum et al 21 reported that the number of filled seeds per panicle is associated with yield of rice.…”
Section: Resultsmentioning
confidence: 99%
“…The number of panicles ranges between 9.6 (HB4) and 27.3 (HB2) panicle per plant. The average number of seeds per panicle, the most importance contributor to heterosis for high yielding hybrids 20 , ranges from 158.8 (HB9) to 323.3 (HB7). Seyoum et al 21 reported that the number of filled seeds per panicle is associated with yield of rice.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of elite commercial combinations have been developed, with yield increases ≥20% compared with their inbred counterparts (50). The most popular hybrid combinations are SY63 and LYP9, both of which have been adopted as model systems for studying the molecular mechanism of heterosis for three-line hybrids and two-line hybrids, respectively (51)(52)(53). Despite the great achievements made in rice breeding programs, our understanding of the molecular mechanism of rice heterosis is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are limited by the density and genomic coverage of genetic markers, so the most convincing genomic characterizations of heterosis come from genetic model systems including rice (Oryza sativa), maize, cotton (Gossypium hirsutum), and Arabidopsis (Arabidopsis thaliana). These genomic studies paint heterosis as the cumulative result of many loci that have a mixture of dominant, overdominant, and epistatic effects (Tang et al, 2010;Zhou et al, 2012;Shen et al, 2014;Shang et al, 2015). There is one notable exception to this pattern, a single locus controlling heterosis for yield in tomato (Solanum lycopersicum).…”
Section: Heterosismentioning
confidence: 99%